Fluoroangiografický obraz angioid streaks - Szedélyová, L (Ceska a slovenska oftalmologie, 1996)
Author observed two patients affected by Pseudoxanthoma elasticum with different extent of alternation on the eye background. The separate states of progression of this eye disease are observed by fluorescein angiography. Beside the finding of angioid streaks fluorescein angiography more precisely demonstrates extent of Bruch membrane abnormalities and alteration of pigmentary epithelium of the retina. This way fluorescein angiography significantly contributes to clarification of other accompanying pathology of this eye disease.
Keywords: pseudoxanthoma elasticum; Pseudoxanthoma Elasticum; angioidní proužky; lidé středního věku; lidé; Female; mužské pohlaví; Fluorescein Angiography; Male; fluoresceinová angiografie; Middle Aged; ženské pohlaví; Angioid Streaks; Humans